A comparison of low volume `high-intensity-training` and high volume traditional resistance training methods on muscular performance, body composition, and subjective assessments of training - Giessing, J.; Eichmann, B.; Steele, J.; Fisher, J. (Biology of Sport, 2016)
Most studies of resistance training (RT) examine methods that do not resemble typical training practices of persons participating in RT. Ecologically valid RT programs more representative of such practices are seldom compared. This study compared two such approaches to RT. Thirty participants (males, n=13; females, n=17) were randomised to either a group performing low volume `High Intensity Training` (HIT; n=16) or high volume `Body-building` (3ST; n=14) RT methods 2x/week for 10 weeks. Outcomes included muscular performance, body composition, and participant`s subjective assessments. Both HIT and 3ST groups improved muscular performance significantly (as indicated by 95% confidence intervals) with large effect sizes (ES; 0.97 to 1.73 and 0.88 to 1.77 respectively). HIT had significantly greater muscular performance gains for 3 of 9 tested exercises compared with 3ST (p < 0.05) and larger effect sizes for 8 of 9 exercises. Body composition did not significantly change in either group. However, effect sizes for whole body muscle mass changes were slightly more favourable in the HIT group compared with the 3ST group (0.27 and -0.34 respectively) in addition to whole body fat mass (0.03 and 0.43 respectively) and whole body fat percentage (-0.10 and -0.44 respectively). Significant muscular performance gains can be produced using either HIT or 3ST. However, muscular performance gains may be greater when using HIT. Future research should look to identify which components of ecologically valid RT programs are primarily responsible for these differences in outcome.